The influence of fuel properties on particulate number emissions from a direct injection spark ignition engine - Leach, F; Stone, R; Richardson, D (SAE International, 2013)
The use of direct injection spark ignition (DISI) engines for passenger cars has increased; providing greater specific performance and lower CO 2 emissions. DISI engines, however, produce more particulate matter (PM) emissions than Port Fuel Injected (PFI) engines. Forthcoming European exhaust emissions legislation is addressing concerns over health effects of PM emissions. Accordingly, research into PM emission formation has increased. A model developed by Aikawa et al. (2010) for PFI engines correlated PM number emissions with the vapour pressure and the double bond equivalent (DBE) of the components of the fuel. However there was no independent control of these parameters. This study investigates a particulate emissions index for DISI engines. A single-cylinder optical access Spray Guided DISI engine was used to develop a Particulate Matter Number emissions Index (PN index) - modified from the PM index using industry standard measurements - through the use of model and commercially available fuels. Model fuels were designed using Raoult's law and UNIFAC such that the DBE and vapour pressure of the fuel mix could be varied. Engine tests were conducted, independently varying the DBE and the vapour pressure of the fuel. PM number emissions were measured using a Cambustion DMS500, the results were analysed alongside observations of the fuel spray to investigate the PN index. The PN index has also been used to evaluate emissions from two commercially available EN228 fuels. The results demonstrate that the trend of the PN index is followed both with model fuels and commercial gasolines.